2016
DOI: 10.1007/s12192-015-0642-8
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 fatty acids differentially modulate enzymatic anti-oxidant systems in skeletal muscle cells

Abstract: During physical activity, increased reactive oxygen species production occurs, which can lead to cell damage and in a decline of individual's performance and health. The use of omega-3 polyunsaturated fatty acids as a supplement to protect the immune system has been increasing; however, their possible benefit to the anti-oxidant system is not well described. Thus, the aim of this study was to evaluate whether the omega-3 fatty acids (docosahexaenoic acid and eicosapentaenoic acid) can be beneficial to the anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 52 publications
0
21
0
1
Order By: Relevance
“…Omega-3 polyunsaturated fatty acids (PUFAs) are long chain PUFAs found in marine sources as shrimp, fish, mussel, oyster, [13] , nuts and sesame seeds [14] , flax seed and vegetable oils such as soybean, canola and olive [15] . It has been found that the benefits of Omega-3 (PUFAs) could be due to reduction in the production of pro-inflammatory cytokines, act as antioxidant and immune system protection [16] . The protective health effects of omega-3 fatty acids were described first in the Greenland Eskimos who consumed a high seafood diet and had low rates of coronary heart disease, asthma, type 1 diabetes mellitus, and multiple sclerosis [17] .…”
Section: Introductionmentioning
confidence: 99%
“…Omega-3 polyunsaturated fatty acids (PUFAs) are long chain PUFAs found in marine sources as shrimp, fish, mussel, oyster, [13] , nuts and sesame seeds [14] , flax seed and vegetable oils such as soybean, canola and olive [15] . It has been found that the benefits of Omega-3 (PUFAs) could be due to reduction in the production of pro-inflammatory cytokines, act as antioxidant and immune system protection [16] . The protective health effects of omega-3 fatty acids were described first in the Greenland Eskimos who consumed a high seafood diet and had low rates of coronary heart disease, asthma, type 1 diabetes mellitus, and multiple sclerosis [17] .…”
Section: Introductionmentioning
confidence: 99%
“…Segundo Neto (2011) o exercício físico pode induzir varias adaptações fisiológicas, bioquímicas e psicológicas em indivíduos treinados (4). Da Silva (2015) sustenta a hipótese de que o exercício físico intenso e extenuante causa dano muscular, sobrecarga no SI, gera uma grande quantidade de EROs e que uma dieta antioxidante pode diminuir esses danos favorecendo a recuperação (27). Contudo, os resultados do presente estudo não corroboram os achados de Da Silva, uma vez que as respostas do SI não foram modificadas pela suplementação de antioxidantes, mesmo durante um período de treinos extenuantes.…”
Section: Resultsunclassified
“…Notably, Johnson et al (2015) have demonstrated that EPA, but not DHA, attenuated the age-related loss of mitochondrial function in skeletal muscle of old mice [15]. Moreover, it has been shown that DHA and EPA also influenced expression of anti-oxidant enzymes of mouse skeletal muscle cells [17] and decreased mitochondrial reactive oxygen species (ROS) production in skeletal muscle of older adults after four months of a n-3 PUFA (mix of EPA and DHA) dietary intervention [18]. Therefore, mitochondrial metabolism seems to be a prime target for the beneficial effects of n-3 PUFAs during 4 aging.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, mitochondrial metabolism seems to be a prime target for the beneficial effects of n-3 PUFAs during 4 aging. However, aging is a progressive process and contradictory results exist in the literature about the effects of either EPA or DHA on mitochondrial functions [15][16][17][18]. We hypothesized that these discrepancies can partly be explained by (i) the fact that EPA and DHA can be interconverted, which makes difficult to pinpoint their specific effects, (ii) the model used, as the experimental time-frame to evaluate the effects of n-3 PUFA in the context of aging can be problematic in rodents or humans.…”
Section: Introductionmentioning
confidence: 99%